Molecular epidemiology of methicillin-resistant Staphylococcus aureus in Gulf Cooperation Council countries (2010–2025): a scoping review - Briki, Ahmed; Alkhatib, Nada; Aloba, Bisola; Verma, Subham; Nassar, Rania; Everett, Dean; Ehricht, Ralf; Monecke, Stefan; Senok, Abiola (Frontiers in Microbiology, 2025)
BackgroundMethicillin-resistant Staphylococcus aureus (MRSA) is a global public health concern, including within the Gulf Cooperation Council (GCC). As an opportunistic pathogen, MRSA poses a threat to hospitalized patients, and to the wider community. Its success is largely attributed to its diverse virulence factors and adaptability, with antimicrobial resistance further enhancing its persistence and complicating treatment efforts. In the GCC, the epidemiology of MRSA is influenced by several distinctive factors, including the region’s diverse demographics, high population mobility, and variations in healthcare infrastructure. Understanding the molecular epidemiology is crucial to curb transmission and guide effective public health measures.AimThis scoping review evaluates MRSA data in GCC countries—United Arab Emirates (UAE), Saudi Arabia, Kuwait, Qatar, Oman, and Bahrain—focusing on prevalence trends, molecular characteristics, and gaps in the literature.MethodsA systematic search of the PubMed (National Library of Medicine [NLM], National Institutes of Health [NIH]) database was conducted to identify literature published between January 2010 and July 2025, using predefined keywords on MRSA epidemiology. Eligible studies were reviewed for MRSA prevalence, clonal diversity, antimicrobial resistance patterns, and virulence profiles.ResultsOf 864 records screened, 97 met the inclusion criteria and were subjected to detailed review. Most studies originated from Saudi Arabia (58%), followed by Kuwait (26%), UAE (7%), Oman (3%), Qatar (2%), Bahrain (2%), and two involving adjacent countries (2%). Data indicate a predominance of community-associated MRSA (CA-MRSA) across both healthcare and community settings. Several studies reported novel or rare MRSA strains across various GCC countries. Moreover, there is clear evidence of widespread resistance to multiple classes of antibiotics, highlighting the growing concern of multidrug-resistant MRSA. Increasing prevalence of strains with virulence/resistance genes such as pvl and SCCmec+fusC, associated with enhanced pathogenicity and resistance, was also observed. Along with wide clonal diversity, frequent travel, and differing infection control practices contribute to the region’s complex MRSA epidemiology.ConclusionMRSA in the GCC shows dynamic and evolving patterns. Continuous surveillance through coordinated regional efforts is essential. A One Health approach, combined with strengthened antimicrobial stewardship, mandatory hospital screenings, and wastewater monitoring, could improve MRSA detection, tracking, and control across the region.